Implementasi Konsep Arsitektur Berkelanjutan pada Fasilitas Desa Wisata Mattabulu - Syarif - Beddu; Triyatni - Martosenjoyo; Syavir - Latif; Rahmi Amin Ishak; Dahniar - -; Teguh Iswara Suardi; Syahriana Syam (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2023)
Sustainable architecture is an architectural work that adopts many materials sourced from the surrounding nature, the technical construction is easy to apply by local craftsmen and does not require specific skills. Mattabulu Village has been designated by the Soppeng Regional Government as a Tourism Village, and strengthened by the decision of the Minister of Tourism and Creative Economy, for the award as an Indonesian Tourism Village 2021. The main purpose of this service is to assist partners as managers of the Village-Owned Enterprises "Pada Ati" in the design of building facilities- tourist facilities. The theoretical study of sustainable architecture will be implemented into the basic concept of developing each tourist vehicle. The method of applying the concept of sustainable architecture, namely conducting studies and observations of the vehicles that have been built, to what extent the elements that form them have a sustainable concept. The results of the implementation of the application of sustainable architecture, on the tourist vehicle will have an impact on the architectural appearance that is "unified" (synergized) with the natural surrounding environment. The conclusion or achievement of this service is to help the community (Bumdes Pada Ati), to implement sustainable architecture on tourist attractions in Mattabulu Village.